Immediate breast reconstruction is oncologically safe for node-positive patients: Comparison using propensity score matching. Issue 36 (10th September 2021) - Oda, Goshi; Nakagawa, Tsuyoshi; Uemura, Noriko; Mori, Hiroki; Mori, Mio; Fujioka, Tomoyuki; Onishi, Iichiroh; Uetake, Hiroyuki
Abstract : Abstract: The oncological safety of immediate breast reconstruction (IBR) in lymph node-positive patients is unclear. In the present study, the impact of IBR on recurrence based on data of patients with axillary lymph node metastases only was examined. The subjects were 232 patients who underwent breast surgery. The patients were grouped into 2 cohorts: non-IBR patients who underwent mastectomy with axillary lymph node dissection; and IBR patients with tissue expander or flap transfer and axillary lymph node dissection. The Non-IBR group included 165 patients, and the IBR group included 67 patients. For the comparison of oncological outcomes between the 2 groups, propensity score matching was performed. The propensity scores were calculated by logistic regression analysis, including age, tumor staging, human epidermal growth factor receptor 2 status, and estrogen receptor status. There was no difference in locoregional recurrence-free survival (LRRFS) between the non-IBR and IBR groups. The 5-year LRRFS rate was 78.9% in the non-IBR group and 85.1% in the IBR group. There was no difference in recurrence-free survival (RFS) between the non-IBR and IBR groups. The 5-year RFS rate was 75.6% in the non-IBR group and 78.8% in the IBR group. In all patients, the 5-year LRRFS rate was 77.3%, and the RFS rate was 70.5%. Multivariate Cox regression analysis to identify factors affecting RFS in all patients showed that estrogen receptor status and high nuclear grade were significant prognostic factors; IBR was irrelevant. This is the first report of an analysis using propensity score matching limited to node-positive breast cancer patients, and it showed that IBR is relatively safe in such patients.